Pengaruh Penggunaan Protein dan Kultur Khamir Dalam Ransum Terhadap Mortalitas Embrio Ayam Arab - Natsir, Nur Alim (Biosel Biology Science and Education, 2020)
Protein is an important nutrient in the diet. The availability of protein in the diet is absolutely necessary as a source of building blocks for growth, replacement of damaged tissue and maintaining reproductive functions. In the preparation of a perfect ration, the balance of energy and protein, amino acids need to be considered because they determine the productivity and reproduction of chickens. The purpose of this study was to determine the effect of the use of protein and yeast culture in the ration on the mortality of Arabic chicken embryos. The observed effects include the interaction effect and the single effect of protein level and yeast culture in the ration on the mortality of Arabic chicken embryos. The research material is as many as 240 "Arabic Chickens" aged 28 weeks as experimental animals. Hatch eggs produced during the study (at the age of 28 to 36 weeks of production). The research method used is an experimental method with a completely randomized design with a factorial pattern of 3 x 4 with 5 replications. The treatments given were isocaloric ration (2850 kcal/kg) with different protein content (13%, 15% and 17%) and yeast culture with concentrations (0%; 0.2%; 0.4%; and 0.6 %). Ration and drinking water are provided ad libitum. Data analysis using ANOVA with further testing using Duncan's Multiple Range Test (Duncan's Multiple Range Test). he results showed that the level of protein use 13%, 15% and 17% did not interact with yeast culture 0%; 0.2%; 0.4%; and 0.6% on embryo mortality (P>0.5). However, the single effect of protein or yeast culture in the diet, individually gave a significant effect on embryo mortality (P